EFL Teachers’ Perspectives on Implementing 6C Skills in Indonesian Classrooms - Iin Bulkis; Muhammad Tahir; Geminastiti Sakkir (International Journal of Language, Education, and Literature, 2025)
This study aimed to examine the implementation of 21st-century 6C skills (Critical Thinking, Creativity, Collaboration, Communication, Citizenship, and Character) in EFL classrooms, focusing on teachers' perceptions. The research theories were grounded in social constructivism by Vygotsky (1978) and language teacher cognition by Borg (2003) to frame the understanding of learning processes and skill development. Using a qualitative approach, the research collected data through classroom observations, semi-structured interviews, and document analysis. Two experienced EFL teachers from SMPN 27 Makassar, Indonesia participated in the study. Findings revealed that teachers perceived 6C skills as crucial for developing students' global competence. The study highlights the need for targeted teacher professional development, enhanced school resources, and policy adjustments to effectively integrate 6C skills in EFL instruction.